Reliability, interrelationships, and minimal detectable changes in strength and power metrics among well-trained rugby sevens players - Washif, Jad; Hébert-Losier, Kim; Gill, Nicholas; Zainuddin, Mazwan; Nasruddin, Nur; Zakaria, Ahmad; Beaven, Christopher (Biology of Sport, 2024)
Despite the importance of strength and power in rugby skills and match outcomes, there exists a noticeable gap in the measurement consistency and estimation of a true change of typical assessments designed to assess these qualities. To address this gap, we investigated the between-session reliability, interrelationships, and minimal detectable changes (MDC) of commonly used strength and power measures in team sports. Sixteen national-level rugby 7 s players were tested on two occasions, one week apart. Both the best and average (of 2–3 trials) peak force, peak power, height, distance, and/or strength indices during countermovement jump (CMJ), drop jump (DJ), isometric mid-thigh pull (IMTP), plyometric push-up (PPU), and standing long jump (SLJ) were obtained. Furthermore, one-repetition maximum (1RM) strength for bench press and back squat, reactive strength index, and dynamic strength index were also determined. Reliability was assessed using intraclass correlation coefficients (ICC) and coefficients of variation (CV), and used for MDC calculations, and interrelationships between variables were determined using correlation coefficients. Reliability was excellent for bench press, back squat, and SLJ (ICCs > 0.91); high to excellent for IMTP peak force, all CMJ, and DJ (except best DJ height and contact time), and PPU peak force parameters (ICCs > 0.78), with < 10% CVs (except PPU peak power). MDCs were generally smaller for average than best values. Large to very large relationships (r = 0.60 to 0.85) were observed between bench press, back squat, and IMTP with selected parameters of CMJ and PPU (p < 0.05), but not in DJ and SLJ. In conclusion, selected measures of strength and power displayed high to excellent reproducibility, with average values (rather than best) offering more stable assessments, and “smaller” MDCs. Based upon the relationships, it can be inferred that maximising strength would likely contribute to enhanced explosive performance.